Surgical aspects of pediatric abdominal pain in the era of COVID-19: clinical consideration and outcomes - Abo-Halawa, Nezar; Negm, Mohamed A.; Arafa, Mohamed; Fathy, Mohamed (Frontiers in Pediatrics, 2024)
BBackground: Acute abdominal pain in pediatrics is a medical emergency that requires special attention. During COVID-19 pandemic, this disease presented in pediatric age by different presentations including abdominal presentations.The affected children are presented with abdominal pain, which may be caused by surgical causes or by the virus itself that necessitate surgical consultation. Purpose: This study highlights the impact of the coronavirus pandemic on pediatric patients with acute abdominal pain regarding the presentation, clinical evaluation, and surgical management. Methods: A retrospective cohort study was done through the collection of data from medical records and authors' data repositories of pediatric patients presented with acute abdomen from March 2020 to March 2022, in three pediatric surgery tertiary centers. Results: Eighty-four pediatric patients with acute abdominal pain were included in this study. The diagnosis of acute appendicitis was found in 31 patients (36.9%). Generalized abdominal pain was noted in 17 patients (20.2%) and presentation mimicked acute cholecystitis was occured in 14 patients (16.7%). ultrasonography revealed intussusception in 12 cases (14.3%). Multisystem inflammatory syndrome in children (MIS-C) was present in 9 cases (10.7%) and only one case of pancreatitis (1.2%). Conservative management was successful in 66 cases (78.6%), while operative intervention was needed in18 cases (21.4%). Conclusion: During the COVID-19 pandemic, acute abdominal pain in children was frequently observed. Careful follow up is critically important as most cases do not necessitate surgical intervention. It is crucial to consider COVID-19 as a differential diagnosis in children presenting with acute abdominal pain, particularly in cases of atypical appendicitis and intussusception to prevent unnecessary surgical procedures. Keywords: Acute abdominal pain, pediatric, COVID-19, appendicitis, multisystemic inflammatory syndrome in children (MIS-C)